Juridical Study of Legal Certainty in Determining Land Prices in the Implementation of Land Sale and Purchase Agreements According to the Land Sale and Purchase Deed and Determination of the Batam City Regional Revenue Agency - Kurniawan, Deni (Jurnal Konstatering, 2024)
Determining the price of land for tax administration purposes and issuing land ownership certificates experiences a difference between the price agreed upon by the parties and stated in the Deed of Sale and Purchase and the price determined by the Regional Revenue Agency in Batam City. The approach method used in this qualitative legal research is the sociological juridical approach, namely an approach that seeks information through direct interviews with informants empirically first and then continues by conducting secondary data research contained in literature studies through theoretical steps. The implementation of land price determination based on the land sale and purchase agreement deed in Batam is currently experiencing a difference between the price agreed upon by the parties carrying out the land sale and purchase as then outlined in the AJB and the price determined by BAPENDA in Batam City.